Food fortification and iron deficiencyanaemia – school model approach - E.LAKSHMI (International Journal of Pharma and Bio Sciences, 2016)
Food based approaches are gaining high potential for long lasting benefits in improving nutrition and serum iron status of adolescents. The study assessed the impact of nutrition education and intervention of a novel iron rich fortified beet-root extract on the packed cell volume(Haematocrit) and weight gain of adolescents. 80 study participants (Haemoglobin<9gm/dl) were randomly assigned to two study groups the intervention and control. 150ml of the fortified beetroot extract was served to each of the interventional subjects on every alternate days for three months (45days). Control group was served with a placebo. Nutrition education was given (n=80).Packed cell volume (Haematocrit) and weight gain were assessed. Students paired ‘t’ test was performed to test the level of significance. Hypothesis was tested at 95 per cent confidence interval. The mean body weight improved significantly (t=3.42, p<.0001) in the intervention group (13-15yrs) with significant (t=18.8, p< .0001) impact in the mean Packed cell volume (16-18yrs). In conclusion fortified beet-root extract intervention had high impact on the body weight and packed cell volume of adolescents.